The EpiNo® Device: Efficacy, Tolerability, and Impact on Pelvic Floor-Implications for Future Research - Tilemachos Kavvadias; Irene Hoesli (Hindawi Limited, 2016)
Aims. The aim of this review is to provide a comprehensive overview of the available literature on preventing perineal trauma with the EpiNo. Methods. We perfomed a literature research in the MedLine and EMBASE databases for studies referring to EpiNo published between 1990 and 2014, without restrictions for language and study type. Results. Five published studies were identified, regarding the effect of EpiNo on the rate of episiotomy and perineal tears, pelvic floor muscle function, and fetal outcome. The device seems to reduce episiotomy and perineal tears' rate, as well as the risk for levator ani microtrauma and avulsion, though not always statistically significant. It does not seem to have an effect on duration of second stage of labour and fetal outcome. The device is well tolerated and the adverse events are rare and mild. However, design and reporting bias in the reviewed articles do not allow evidence based conclusions. Conclusions. The EpiNo device seems to be promising, with potential positive effects on natural birth, while being uncomplicated to use and without major complications. Well designed, randomized trials are needed in order to understand the effects of EpiNo on pelvic floor and make evidence based recommendations on its use.